Director remuneration, family ownership and firm performance: an analysis from Malaysian listed firm for period of 2005 till 2013 - Ab Razak, Nazrul Hisyam; Palahuddin, Salmi Huwaina (Corporate Ownership & Control, 2017)
This study examines the association between directors' remuneration, corporate governance structures and firm performance of 140 Malaysian listed firms which 70 firms are family firm and 70 firms are non-family. Data has been collected through annual reports in Bursa Malaysia's database from 2005 till 2013. The results show that firm performance is positively and significantly related to directors' remuneration, firm's growth and size measured by ROA, ROE and Tobin's Q. However, firms' performance in this study is not responsive to anticipated future market valuations in Stock returns. The study also finds that family ownership leads to lower performance than non-family owned firms on accounting measurement (ROA and ROE) and market measurement (Tobin's Q) after controlling company specific characteristics. The findings also reveal that role duality has no significant effect on accounting and market performance. Meanwhile the study explores that firm performance is negatively and significantly related to leverage. The findings can be useful to regulators to limit director's influence over remuneration packages especially in family firm. The study also contributes to the growing literature on executive and directors' remuneration and it provides international evidence on the effects of corporate governance reforms in recent years in influencing boardroom remuneration and ownership structure on a firm's efficiency and performance.